Genotypic Variability in Tomato for Total Carotenoids and Lycopene Content during Summer and Response to Post Harvest Temperature - K S Shivashankara (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
Lycopene is the major carotenoid responsible for fruit colour in tomato (Lycopersicon esculentum Mill.). However, colour of the fruit is greatly affected by high temperature prevailing during fruit growth in the summer crop. To select a genotype suitable for summer conditions that can maintain colour better, a set of 52 tomato genotypes were evaluated for lycopene, total carotenoids and for TSS during summer in Bengaluru. Among the genotypes screened, IIHR 2892 recorded very high lycopene content (328.4mg/100g dry weight) and IIHR 2866 recorded very low lycopene content (25.2mg/100g dry weight). TSS values ranged from 2.6° Brix in cv. Vybhav to 7.0° Brix in IIHR 2866. In addition, study was carried out to determine the effect of postharvest temperature on biosynthesis of lycopene in five selected tomato cultivars (Arka Rakshak, Arka Samrat, Arka Ananya, Lakshmi and Abhinava). Tomatoes harvested at breaker stage were stored at 27° C, 35° C and 40° C for ripening. High temperature reduced lycopene content in tomato fruits. Lycopene synthesis in fruits was completely inhibited above 35°C. In this study, mean lycopene content in tomatoes stored at 27° C was 3-4 times higher than that in tomatoes stored at 40° C. This indicates that in tomatoes, temperature at which the fruits are stored after harvest, is a more important factor for colour development.